LUMBAR SPINAL CANAL STENOSIS, DIAGNOSTIC AND MANAGEMENT - Putu Indah Budi Apsari; I Ketut Suyasa; Sri Maliawan; Siki Kawiyana (E-Jurnal Medika Udayana, 2013)
Lumbar spinal canal stenosis is a narrowing of the osteoligamentous vertebral canal and/or the intervertebral foramina causing compression of the thecal sac and/or the caudal nerve roots. The prevalence are five per 1000 person over 50 years old in USA. Male more than female, the most affect L4 -L5 and L3-L4. Low back pain is the most symptom. Routine diagnostic examination can be done plain x-ray lumbosacral, CT scan, and MRI. Management therapy can divide to two conservative and operative therapy. Complication of operative therapy is infection, vacular injury, cardiorespiratory disturbance due to embolization and death. The prognosis related with severity of symptom, degree of stenosis, surgical procedure and comorbid conditions.